Utilization of Jack Bean Seed (Canavalia ensiformis) with Treatments of Protease Enzyme Fed to Broiler in Starter Period - Brahmadhita Pratama Mahardhika; Muhammad Ridla; Rita Mutia; Iyan Yuliana; Miftakhun Naja (Faculty of Animal Science, Universitas Brawijaya, 2021)
The achievement of this study was to evaluate the use of jack bean seed and protease enzymes in different protein levels in the Broiler ration on performance and metabolizable energy. Two hundred and forty broilers were distributed into 3 object factors and 3 replications. The first factor was the difference of the ingredients (soybean meal-based basal ration and jack bean seed-contained rations), the second factor was the level of protein (22% and 19.5%) and the third factor was the enzyme treatment (without enzymes and with the inclusion of the proteases). A total of 2 birds from each treatment were assigned as a sample for metabolizable energy assay. The experimental design used was a factorial completely randomized design (FCRD). The data were analyzed using Analysis of Variance (ANOVA). The results showed that adding jack bean seed into the Broiler starter’s ration significantly (P <0.01) decreased the body weight gain (BWG) but it could be improved with the inclusion of protease enzyme. The metabolizable energy of the ration containing jack bean seed was significantly higher (P<0.01) than in the basal ration. The use of a low protein level ration (19.5%) significantly (P <0.01) showed the decrease in BWG, decrease in true metabolizable energy, and true corrected-nitrogen metabolizable energy but could be improved with the addition of protease enzyme. The use of the protease enzyme could improve the performance of broiler chickens fed with a low protein ration that contained Jack bean seed (Canavalia ensiformis).